Karikatur Humor dan Pembelajaran Bahasa Interkultural: Tinjauan Literatur dalam Konteks BIPA - Fahrani Almira Rizkya Haryanto; Lely Nur Tachi; Salsabyla Nurul Khanifah; Laily Nurlina (Ruang Kata, 2026)
BIPA learning in the current era requires an approach that is not only oriented in mastering the structure but also in understanding culture and communication contexts. One of the main challenges in BIPA learning is the limitation of teaching media that is able to integrate linguistic and cultural elements simultaneously. This study aims to examine the role and potential of humor caricatures as an intercultural learning medium in the context of BIPA. The focus of the study is directed at the contribution of humor caricatures in supporting the development of communicative competence, cultural sensitivity, and pragmatic understanding of foreign learners. The research method used is a literature review with a descriptive qualitative approach. The data sources are in the form of scientific articles, books, and research reports relevant to the topics of caricature, visual humor, multimodality, and intercultural language learning published in the period 2014–2024. The data was analyzed descriptive-interpretively through the stages of thematic grouping, concept interpretation, and synthesis of previous research findings. The results of the study show that humor caricatures have a function more than just an entertainment medium. Caricatures are able to represent social values, cultural criticism, and local symbols that help BIPA learners understand the context of Indonesian use more fully. In addition, the use of humor caricatures has been proven to increase intercultural sensitivity, critical thinking skills, and visual literacy of learners. The conclusion of this study confirms that humor caricatures are worthy of being developed as an innovative learning medium in BIPA because they are able to bridge language and culture contextually. The integration of this media has the potential to create more reflective, communicative, and meaningful learning